(untitled) (Studia Prawnicze / The Legal Studies, 1980)
The family and guardianship code of 1964, similarily to the family code of 1950, does not mention the defects in the declaration of will as of condition of validity of marriage. Thus, there arises a problem of how to understand the change of position of the legislature which mentioned several defects of a consent to marry (such as mistake as to the person, duress, lack of understanding or liberty in decision-making) in the legal acts previously binding. The Supreme Court and a part of the legal doctrine represent the view according to which the defects in the declaration of will of the parties to marry have no influence on the validity of marriage, although they can constitute an important reason of desintegration of matrimonial life and thus constitute a reason of divorce. This view, and especially shifting the problem from the defects of a declaration of will to the issue of "divorce, rises many doubts. In the light of binding provisions of the family law any other interpretation is however incorrect and de lege lata validity of existence of marriage cannot be made dependent upon correctness of a consent to marry. On the other hand, de lege feTenda it seems just to introduce into the family and guardianship code the catalogue of the defects of declaration of will, such as mistake as to the identity of a natural person, duress, lack of understanding or lack of liberty in decision-making. This suggestion is especially due to the provisions of New York Convention of 1962 on consent to conclude a marriage as well asto the Pact of Rights of Man and Citizen which provide that a marriage cannot be legally concluded without a full consent of both parties expressed at liberty. This principle cannot be directly applied in Polish family law because of the lack of provisions concerning the grounds of divorce or the title to appear before the court or convalidation of marriage in the above mentioned international agreements. However, it creates for Poland an obligation to make adequate changes in internal legislation. The issue of a consent to marry is treated in a different way in Polish private international law. In relations between countries members of the New York Convention or of the Pact of Rights of Man and Citizen, defectiveness of a declaration of will acts in principle in two ways. This means for example, that a Polish citizen who was mistaken as to the person of hiS spouse — citizen of the Federal Republic of Germany — will be able to seek dissolution of a marriage according to the provisions of the national law of the latter (lex patriae).